Propostas de ações de difusão para o acervo fotográfico do Museu da Cidade do Rio Grande - RS - Santos, Sara Orcelli dos (2014)
This dissertation is presented as the result of the master's research developed at the Professional Postgraduate Program in Cultural Heritage from the Federal University of Santa Maria (PPGPPC/UFSM). The theme oh this work is the diffusion of cultural heritage. As object of the study, we present the photographic collection of the Historical Collection of the Museum of the City of Rio Grande - RS. The development consists on the study and planning actions for the diffusion of heritage, from the recognition of photographs as Documentary Heritage. Therefore, we present the characterization of the research, its objectives and methods, as well as reflections on the theoretical reference used, encompassing cultural heritage photographs as documentary heritage and the ways and kinds of diffusion. Furthermore, we propose a discussion about the institutional activities that must be performed before implantation of diffusion actions. As the result and product, we present diffusion strategies that integrate the Diffusion Program of the photographic collection of the Museum of the City of Rio Grande, for which we use a sample of the collection, with the theme of Customs and Port of Rio Grande City.